The motivations that put Portugal back on the route of Brazilian higher education students - Iorio, Juliana (2021)
For a long time the historical/colonial relations between Brazil and Portugal guaranteed the mobility of Brazilian elite that wanted to obtain a degree mostly from the University of Coimbra. However, only in the twenty-first century the flow of Brazilian students to Portuguese higher education increased, turning it into the largest community of foreign students in Portugal. This paper will discuss the motivations that, since 2008/2009 (the school year in which, according to data from the General Directorate of Education and Science Statistics – DGEEC – in Portugal, the supremacy of this community over the others was verified), have put Portugal back on the route of Brazilian higher education students.